The “Twin Paradox” Resolved - James Arnold (European Scientific Journal, ESJ, 2016)
The so-called “Twin Paradox”, wherein a relativistic effect is hypothesized to produce verifiably different clock rates between bodies, has not been resolved to the satisfaction of many theorists. There has been an abiding difficulty with determining how arbitrary periods of uniform motion, when both twins will observe the other’s clock to move more slowly, can be resolved upon their reunion. Spacetime diagrams are used here to demonstrate visually and mathematically that there is a nonparadoxical explanation for the supposed discrepancy that has not been previously proposed.